Understanding international student migration: the case of Nigerian Christian women students engaged in postgraduate studies in UK higher education - Oluwaseun, Stella (2016)
This thesis explores the motivations and lived experiences of Nigerian Christian women engaged in postgraduate studies in UK higher education based on 20 semi-structured interviews. For this group of women, their educational quest abroad is happening at the phase in the normative life course when they are expected by Nigerian society to be wives as well as mothers. Such cultural expectations carry social sanctions for non-conformity.